INTEGRATION OF OPERATIONAL MANAGEMENT, DIGITAL MARKETING, AND PRODUCT INNOVATION IN ENHANCING THE COMPETITIVENESS OF HFC IN THE DIGITAL ECONOMY ERA - Stanley Prabowo; Sunarto Budiono; Agung Winarno (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze and integrate three strategic pillars essential to strengthening the competitiveness of micro, small, and medium enterprises (MSMEs): operational management, digital marketing, and product innovation. The research adopts a case study of Hafiza Fried Chicken (HFC) as a representative culinary MSME operating in the digital economy era. The study is grounded in the urgency of enhancing MSMEs’ adaptive capacity toward digital transformation and managerial efficiency to ensure business sustainability. A qualitative descriptive approach was employed through field studies and in-depth interviews, supported by direct observation of HFC’s operational systems and digital marketing activities during a five-week intensive mentoring process. Data were analyzed thematically, emphasizing the integration of cross-functional managerial processes within the frameworks of the Resource-Based View (RBV) and Dynamic Capabilities Theory (DCT). The findings reveal that integrating standardized operational management systems with data-driven digital marketing strategies enhances efficiency and service consistency, thereby strengthening customer trust. The implementation of Standard Operating Procedures (SOPs) and digital recording systems reinforces quality control while providing a foundation for informed decision-making. Meanwhile, product innovation developed through the observation of consumer preferences on social media successfully generates value differentiation, contributing to increased revenue and customer loyalty. The integrative model resulting from this research highlights that the synergy between operational efficiency, adaptive digital strategies, and sustainable product innovation serves as a critical determinant of MSME sustainability in the digital economy. Theoretically, the study underscores the importance of a cross-functional management approach as a form of strategic alignment between internal resources and external market dynamics. Practically, it emphasizes the need to strengthen managerial capacity and digital literacy among MSME actors to facilitate their transformation from traditional orientations toward innovation- and data-driven business models. This study offers an empirical contribution to the development of an integrative MSME model in Indonesia, grounded in efficiency, creativity, and sustainability.